IMPLEMENTATION OF ARABIC LANGUAGE TEACHING EVALUATION IN HIDAYATULLAH BATU USING THE CIPP MODEL (CONTEXT, INPUT, PROCESS, AND PRODUCT) - Rotul Khairi, Zur; Wargadinata, Wildana; Hasan, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of the Arabic language teaching program at Ma'had Hidayatullah Batu based on the CIPP evaluation model. The CIPP evaluation model focuses on four aspects; 1) context evaluation 2) input evaluation 3) process evaluation 4) outcome evaluation. The type of approach used is qualitative descriptive evaluative with data collection techniques through observation, interviews, and documentation. The data analysis technique used is the data analysis technique according to Miles, Huberman, and Saldana. The results of this study indicate that, based on; 1) context evaluation, running according to the vision and mission of the school in creating a safe, comfortable, and ideal atmosphere and environment for Arabic language teaching. 2) input evaluation, Arabic language teaching at Ma'had Hidayatullah Batu is supported by adequate input, both from human resources and supporting facilities. 3) process evaluation, there are challenges in practice, such as students who tend to be passive and lack confidence. 4) Evaluation of Arabic language teaching outcomes at Ma'had Hidayatullah Batu shows that students have achieved the highest level of teaching. By the end of the teaching period, some students' language skills, particularly speaking and writing, still needed improvement. This is due to the teaching method, which requires a continuous process and time to develop creativity, communication skills, and thinking abilities.